Panobinostat Effectively Increases Histone Acetylation and Alters Chromatin Accessibility Landscape in Canine Embryonic Fibroblasts but Does Not Enhance Cellular Reprogramming - Moshref, Maryam; Questa, Maria; Lopez-Cervantes, Veronica; Sears, Thomas K.; Greathouse, Rachel L.; Crawford, Charles K.; Kol, Amir (Frontiers in Veterinary Science, 2021)
Robust and reproducible protocols to efficiently reprogram adult canine cells to induced pluripotent stem cells (iPSC) are still elusive. Somatic cell reprogramming requires global chromatin remodeling that is finely orchestrated spatially and temporally. Histone acetylation and deacetylation are key regulators of chromatin condensation, which are mediated by histone acetyltransferases and histone deacetylases (HDACs), respectively. HDAC inhibitors have been used to increase histone acetylation, chromatin accessibility, and somatic cell reprogramming in human and mice cells. We hypothesized that inhibition of HDACs in canine fibroblasts will increase their reprogramming efficiency by altering the epigenomic landscape and enabling greater chromatin accessibility. We report that a combined treatment of panobinostat (LBH589) and vitamin C effectively inhibits HDAC function and increases histone acetylation in canine embryonic fibroblasts in vitro, with no significant cytotoxic effects. We further determined the effect of this treatment on global chromatin accessibility via ATAC-seq. Finally, the treatment did not induce any significant increase in cellular reprogramming efficiency. While our data demonstrate that the unique epigenetic landscape of canine cells does not make them amenable to cellular reprogramming through the proposed treatment, it provides a rationale for a targeted, canine-specific, reprogramming approach by enhancing the expression of transcription factors like CEBP.